Case Report: Ocular paroxysmal non-epileptic events as the presenting sign of celiac disease in children: a case series - Monzani, Alice; Genoni, Giulia; Papa, Amanda; Paggi, Noemi; Capra, Eleonora; Brustia, Francesca; Rabbone, Ivana (Frontiers in Pediatrics, 2024)
Introduction: Neurologic manifestations may be presenting signs of celiac disease (CD). Pediatriconset paroxysmal non-epileptic events (PNEEs) are not included among them. Cases presentation: We report the case of two children who presented with ocular PNEEs in association with mild symptoms evocative for CD, who were subsequently diagnosed with CD and experienced regression of PNEEs on a gluten-free diet. Data from 12 patients undergoing neurological evaluation in 2019-2023 for ocular PNEEs were reviewed: 3 (25%) had a subsequent diagnosis of CD. Conclusions: Ocular PNEEs could be a presenting manifestation of CD. In the diagnostic work-up of PNEEs, screening for CD could be included, both to avoid unnecessary tests and to promptly start a gluten-free diet, which might lead to a favorable clinical response.